INFLUENCE ON THE POSITIONING AND WEB DESIGN OF THE COMPANY EUROPERÚ S.A.C. BASED ON SEO METHODOLOGY - Wilson LAZO, Gabriel RODRIGUEZ, Wilver AUCCAHUASI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The project consists of the implementation of the SEO methodology to the website of the company Europeru S.A.C under the brand name "modaGuiss" with the aim of generating a presence on the internet and positioning it in the first Google search results; to increase the passive and active traffic of the page and therefore, increase in potential customers, interactions, followers, etc.. Finally, the web application “ModaGuiss | Footwear and Shoes ”starting from the design of the page through the analysis of the competition with free tools for searching and filtering meta information for subsequent implementation of indexing in the consoles of the aforementioned search engines. With what was obtained as a result, appear in the search results with the words: ModaGuiss, Zapatos Guiss, Zapatos Huancayo, etc.. However, to climb positions it was necessary to generate backlinks to our page and maintain constant activity. At the end of the development of the web app and the positioning, good results were obtained such as the positioning of the brand and domain name, by comparing the page without SEO and the page created with SEO, it was possible to specify that the SEO methodology allows you to position quickly in search engines, unlike not using it, which takes months or years to position your page.